Proceedings of the 10th National Technical Seminar on Underwater System Technology 2018 NUSYS'18 - Md Zain, Zainah; Ahmad, Hamzah; Pebrianti, Dwi.; Mustafa, Mahfuzah; Abdullah, Nor Rul Hasma; Samad, Rosdiyana; Mat Noh, Maziyah; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents cutting-edge research papers in the field of Underwater System Technology in Malaysia and Asia in general. The topics covered include intelligent robotics, novel sensor technologies, control algorithms, acoustic signal processing, imaging techniques, biomimetic robots, green energy sources, and underwater communication backbones and protocols. The book showcases some of the latest technologies and applications developed to facilitate local marine exploration and exploitation. It also addresses related topics concerning the Sustainable Development Goals (SDG) outlined by the United Nations. .
Keywords: Signal processing; Physical geography; Control engineering; Robotics; Automation; Signal, Speech and Image Processing; Earth System Sciences; Control, Robotics, Automation